Whether Sovereignty?: The Failure of Indonesia in Taking Over Flight Information Region from Singapore 2015-2019 - Nabyla Humaira; Adwani Adwani; M. Yakub Aiyub Kadir (Udayana Journal of Law and Culture, 2021)
The concept of ‘complete and exclusive sovereignty as defined in international and national law remains poses challenges, especially concerning the effort of Indonesia in taking over the Flight Information Region (FIR) from the Singapore context. The management of FIR by Singapore over the Riau Islands of Indonesia was begun during the British colonial period over Malay territory, which partly became a sovereign state of Singapore in 1965. However, under the syndrome of post-colonialism Indonesia has legalized it through the 1995 bilateral agreement between Indonesia and Singapore. On the other hand, since independence, Indonesia has gradually initiated to take over the FIR until the peak time of the 2015 Presidential Instruction which explicitly orders to take over the FIR of Singapore at the latest in the next four years (2015-2019). However, until the end of 2020, there had been no significant progress. This paper critically investigates such failure within the evolving concept of ‘sovereignty through the Third World Approach to International Law (TWAIL) paradigm in terms of the global justice system. It is proved that the meaning of ‘sovereignty in postcolonial states remains a political rhetoric as also known as ‘negative sovereignty’. Hence, this paper contributes to clarifying the meaning of sovereignty in the Indonesian context, so that a new awareness arises to increase the national capacity to take over FIR from Singapore, and hopefully, the ‘complete and exclusive’ meaning of sovereignty can be perceived in near future, for the maximum benefit of people in Indonesia.